Trophic State of The Pekak Lake, Buluh Nipis Village, Kampar District, Riau Province, Based on Nygaard Index. - Gaol, Melinda Juliana Lumban; Siagian, Madju; Dahril, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractNygard Index can be used to determine the trophic state of waters. Calculation of this index is based on the number of phytoplankton species that are belonged to these following groups, namely Chlorococcales, Euglenophyceae, Centric diatom, Myxophyceae and Desmidiaceae. To understand the trophic state of the Pekak Lake, a research has been conducted in March-April 2018. There were 3 sampling stations, namely S1 (in the inlet, from the Kampar River), S2 (in the middle of the lake) and S3 (in the end of the lake). In each station there were two sampling points, in the surface (0.2 m), and 1 Secchi depth (0.75 m). Samplings were conducted 3 times, once/week. Water quality parameters measured were phytoplankton, transparency, temperature, pH, nitrate, phosphate, dissolved oxygen and free carbon dioxide. Results shown that there are 63 species of phytoplankton present, namely Class Chlorophyceae (22 species), Class Zygnematophyceae (16 species), Bacillariophyceae (12 species), Class Euglenophyceae (4 species), and Class Myxophyceae (3 species), and Class Cryptophyceae (1 species). The water quality parameters are as follows: transparency 68.5-76.8 cm, temperature 28-30 0C, pH 5, nitrate 0.05-0.14 mg/L, phosphate 0.06-0.11 mg/L, dissolved oxygen 5.13-6.40 mg/L, free carbon dioxide 8.23-15.48 mg/L. Nygaard Index value of the Pekak Lake was 1.8–2.37, and it can be categorized as mesotrophic to eutrophic.Keywords: Oxbow Lake, Phytoplankton, Mesotrophic, Water Quality.